Koolark Koort Koorliny: reconciliation, art and storytelling in an Australian Aboriginal Community - Johnston, Michelle; Forrest, S. (Aboriginal Studies Press (ASP), 2017)
In Nyungar Country, in the south-west corner of Western Australia, reconciliation has taken a significant step forward as the whole community expe- riences the healing effect of the Carrolup artworks — a collection of 122 drawings and paintings created in the late 1940s by Aboriginal children who had been forci- bly removed from their families and housed in harsh conditions at the Carrolup Native Settlement in the south-west of Western Australia. The artworks were lost for many years and then discovered and returned to Western Australia in 2013. With a Nyungar language title, koolark koort koorliny, which means ‘heart coming home’, the collection has commenced a series of tours and exhibitions throughout Nyungar Country. It has become evident that people are eager to engage with the exhibitions and that they provide the means by which the stories of the children, known as the Stolen Generations, can be shared with the wider community. They demonstrate the healing effect of that storytelling and are a source of pride for the Aboriginal community. The paintings celebrate traditional Nyungar culture and a unique Nyungar style of art. This paper discusses the artworks’ healing impact on the individuals who have experienced the trauma of removal from their fami- lies, and their power to bring black and white communities together in the spirit of reconciliation.